137k views
3 votes
Chapter: Simplification of Linear Expressions with Fractional Coefficients.

Solve the following expression:

Chapter: Simplification of Linear Expressions with Fractional Coefficients. Solve-example-1
User Marimaf
by
5.2k points

1 Answer

7 votes

Explanation:


(1)/(4) (5y + 4) = (1)/(3)(2y - 1) \\ (5y + 4)/(4) = (2y - 1)/(3) \\ 3(5y + 4) = 4(2y - 1) \\ 15y + 12 = 8y - 4 \\ 15y - 8y = - 4 - 12 \\ 7y = - 16 \\ y = ( - 16)/(7) \\ y = - 2.28

Hope it helps

User Dmitry Vyal
by
4.8k points